1994
DOI: 10.1111/j.1467-9817.1994.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Sentence context and meaning frequency effects in children's processing of ambiguous words

Abstract: Nine-and twelve-year-old children named target words which were preceded by sentences ending in words having more than one meaning. Sentences biased the ambiguous word toward its dominant (more frequent) or subordinate (less frequent) meaning. Targets were related to the same meaning as that biased by the sentence, the other meaning, or were unrelated. Targets were presented 0, 300, or 700 ms following the sentence. For both ages, dominant sentences facilitated responses only to the contextually appropriate ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…This explanation is very parsimonious since just a single mechanism, activation, is suf cient to account for a great variety of results on lexical ambiguity, particularly those involving changes in context-based facilitation. Such an account of ambiguity resolution has proved popular in a number of areas, for example, context effects in resolution of lexical ambiguity (Coolen, Jaarsveld, & Schreuder, 1993;Love & Swinney, 1996;Paul, Kellas, Martin, & Clark, 1992;Simpson & Krueger, 1991;Simpson, Krueger, Kang, & Elofson, 1994;Tabossi, 1988); syntactic ambiguity resolution (MacDonald, 1993); the neuropsychological basis of ambiguity (Burgess & Simpson, 1988); and aphasia (Deloche, Seron, Scius, & Segui, 1987).…”
mentioning
confidence: 99%
“…This explanation is very parsimonious since just a single mechanism, activation, is suf cient to account for a great variety of results on lexical ambiguity, particularly those involving changes in context-based facilitation. Such an account of ambiguity resolution has proved popular in a number of areas, for example, context effects in resolution of lexical ambiguity (Coolen, Jaarsveld, & Schreuder, 1993;Love & Swinney, 1996;Paul, Kellas, Martin, & Clark, 1992;Simpson & Krueger, 1991;Simpson, Krueger, Kang, & Elofson, 1994;Tabossi, 1988); syntactic ambiguity resolution (MacDonald, 1993); the neuropsychological basis of ambiguity (Burgess & Simpson, 1988); and aphasia (Deloche, Seron, Scius, & Segui, 1987).…”
mentioning
confidence: 99%
“…For example, Simpson, Krueger, Kang, and Elofson (1994), using a sentence context with long ISI, did not find this effect. That is, children's semantic priming was not greater than that of adults.…”
mentioning
confidence: 97%
“…That is, children's semantic priming was not greater than that of adults. However, whereas Simpson et al (1994) used homographic words, Schwantes et al (1980) used nonhomographic words. This might explain these discrepant results, because homographic words have specific properties (e.g., more than one meaning).…”
mentioning
confidence: 99%
“…There is a great debate, however, about the role of the context in the activation of the meaning of ambiguous words. Some researchers (e.g., Coolen, Jaarsueld, & Schreuder, 1993;Glucksberg, Kreuz, & Rho, 1986;Paul, Kellas, Martin, & Clark, 1992;Schvaneveldt, Meyer, & Becker, 1976;Simpson, 1981;Simpson & Krueger, 1991, Simpson, Krueger, Kang, & Elofson, 1994Tabossi, 1988;Van Petten & Kutas, 1987) propose that the initial activation of the ambiguous word meaning is due to the context, as the context only primes the meaning that is consistent with it, making it unnecessary to access the other meanings. Other researchers (Conrad, 1974;Holley-Willcox & Blank, 1980;Kinoshita, 1985;Kintsch & Mross, 1985;Love & Swinney, 1996;Lucas, 1987;Onifer & Swinney, 1981;Seidenberg, Tanenhaus, Leiman, & Bienkowski, 1982;Simpson & Burgess, 1985;Simpson & Foster, 1986;Swinney, 1979;Tanenhaus, Leiman, & Seidenberg, 1979) have found that when an ambiguous word is presented, all its meanings are activated, and the context selects the meaning consistent with it.…”
mentioning
confidence: 99%